2009
DOI: 10.1364/josaa.26.002183
|View full text |Cite
|
Sign up to set email alerts
|

Explicit finite-difference vector beam propagation method based on the iterated Crank-Nicolson scheme

Abstract: We introduce and develop a new explicit vector beam propagation method, based on the iterated Crank-Nicolson scheme, which is an established numerical method in the area of computational relativity. The proposed approach results in a fast and robust method, characterized by simplicity, efficiency, and versatility. It is free of limitations inherent in implicit beam propagation methods, which are associated with poor convergence or uneconomical use of memory in the solution of large sparse linear systems, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
0
13
0
10
Order By: Relevance
“…One possibility is to have a computational grid to sample the core of the waveguiding structure, and a singlesite boundary layer of "ghost" points that will be slaved to the inner solution in such a way that a discrete approximation to (9) will be satisfied. Such an approach meshes well with Crank-Nicolson-based BPM methods utilizing either sparse or iterative linear solvers, and also with other methods, e.g., the explicit iterated Crank-Nicolson method [27]. We will illustrate an implementation with the method of lines.…”
Section: Boundary Discretizationmentioning
confidence: 88%
See 2 more Smart Citations
“…One possibility is to have a computational grid to sample the core of the waveguiding structure, and a singlesite boundary layer of "ghost" points that will be slaved to the inner solution in such a way that a discrete approximation to (9) will be satisfied. Such an approach meshes well with Crank-Nicolson-based BPM methods utilizing either sparse or iterative linear solvers, and also with other methods, e.g., the explicit iterated Crank-Nicolson method [27]. We will illustrate an implementation with the method of lines.…”
Section: Boundary Discretizationmentioning
confidence: 88%
“…For the reference calculations, we solve the beam propagation equations with the iterated Crank-Nicolson method [27], and calculate quasi-TM modes across a range of wavelengths by propagation in imaginary distance. Then, we compare results obtained in the semivectorial approach, in which the grid is restricted to the silicon nitride core (including the silica slot), and boundary conditions in the form of (16) and (17) are applied.…”
Section: Application To High-contrast Waveguidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also another version of the iterated CN method was proposed in [5] and it was found that the last algorithm has better properties even providing only the first order of accuracy. Different versions of the iterated CN method were used in numerical relativity by a number of authors (e.g., [3,4,[6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Η λύση και στα δύο ζητήματα δόθηκε από τη μέθοδο των πεπερασμένων διαφορών (Finite Difference Method, FDM). Η πρώτη προσέγγιση της διανυσματικής FD-BPM πραγματοποιήθηκε μέσω ενός σχήματος πεπερασμένων διαφορών Crank-Nicolson [116], ενώ έκτοτε προτάθηκαν διάφορες προσεγγίσεις διατύπωσης της μεθόδου διάδοσης δέσμης με τη χρησιμοποίηση διαφόρων σχημάτων πεπερασμένων διαφορών [117][118][119][120]. Εξαιτίας της δυνατότητας για γρήγορη και εύκολη (από πλευράς υπολογιστικών πόρων) επίλυση που παρέχει, η BPM είναι αναμφίβολα μια χρήσιμη εναλλακτική αριθμητικής ανάλυσης, ενώ οι όποιες προσεγγίσεις που εισάγονται κατά την υλοποίηση της μεθόδου (π.χ.…”
Section: πρόλογος Iunclassified